2016
DOI: 10.1117/1.jbo.21.8.080502
|View full text |Cite
|
Sign up to set email alerts
|

Enhancingin vivotumor boundary delineation with structured illumination fluorescence molecular imaging and spatial gradient mapping

Abstract: Fluorescence imaging, in combination with tumor-avid near-infrared (NIR) fluorescent molecular probes, provides high specificity and sensitivity for cancer detection in preclinical animal models, and more recently, assistance during oncologic surgery. However, conventional camera-based fluorescence imaging techniques are heavily surface-weighted such that surface reflection from skin or other nontumor tissue and nonspecific fluorescence signals dominate, obscuring true cancer-specific signals and blurring tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In vivo optical imaging of myeloma using bioluminescent reporters and xenograft models has provided insights into VLA4 expression, survival and tumor cell homing 26 , 61 , 62 . In our studies, LLP2A-Cy5 showed selective VLA4 binding in tumor tissue compared to non-tumor VLA4 expressing tissue by FACS analysis; while overall spleen and BM uptake of LLP2A-Cy5 was significantly higher in the WT 5TGM1-GFP tumor bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo optical imaging of myeloma using bioluminescent reporters and xenograft models has provided insights into VLA4 expression, survival and tumor cell homing 26 , 61 , 62 . In our studies, LLP2A-Cy5 showed selective VLA4 binding in tumor tissue compared to non-tumor VLA4 expressing tissue by FACS analysis; while overall spleen and BM uptake of LLP2A-Cy5 was significantly higher in the WT 5TGM1-GFP tumor bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Early work demonstrated the benefit of optical sectioning in fluorescence using SFDI in turbid systems 68,69 and was recently extended to in vivo imaging. 70 The simple method allows users to preferentially select either long or short pathlengths by varying the spatial frequency of the projection. By changing the spatial frequency of illumination, significant improvements were demonstrated in both lateral and axial resolution when detecting fluorescent inclusions in diffusive media with background contrast.…”
Section: Sfdi and Fluorescencementioning
confidence: 99%
“…Imaging with increased spatial frequency decreases the average collected photon path length, resulting in a decreased average photon penetration depth 21 , 22 , 33 and increased sensitivity to shorter path length interactions 41 , 98 . The spatial pattern can be adjusted during fluorescence imaging to vary the depth and contrast, 33 , 99 , 100 or pushed high such that sensitivity to absorption is lost [cf. Fig.…”
Section: Spatial Frequency-domain Imagingmentioning
confidence: 99%